Adopting Mathematics as A Desired Insrtument for The Reduction Of Corruption In Nigeria - Joseph, Joseph Ugochukwu (Universitas Malikussaleh, 2020)
This paper discussed that mathematics is a valuable subject, as such, it is vital in inculcating good and acceptable behaviours and values among different categories of students in Nigeria. Since corruption is not an acceptable behaviour and there is the need to avoid and prevent it in the society, it was argued that with effective mathematics teaching and learning, students will acquire the knowledge and inherent values of mathematics towards cultivating good and acceptable behaviours. This will help Nigeria to produce well-behaved citizens and to develop in a healthy manner. Some vital concepts in mathematics through which good and acceptable behaviours and values can be inculcated into students discussed in this paper include the critical roles of formulas, logic and mathematical games. The paper concluded that, besides the acquisition of knowledge, mathematics is useful in cultivating good behaviours in students for good the society. It was thereof, recommended that all mathematics teacher should be encouraged to teach the subject very well through the use of practical examples in order to make its learning simple, realistic and interesting for the students. Also, in the course of teaching, they need to give examples of how specific aspects of mathematics could be used to help in moulding the behaviours of students positively